Mother to child transmission of HIV among Zimbabwean women who seroconverted postnatally: prospective cohort study. (22nd December 2010) - Humphrey, Jean H; Marinda, Edmore; Mutasa, Kuda; Moulton, Lawrence H; Iliff, Peter J; Ntozini, Robert; Chidawanyika, Henry; Nathoo, Kusum J; Tavengwa, Naume; Jenkins, Alison; Piwoz, Ellen G; Van de Perre, Philippe; et al.
Abstract : Objectives To estimate the rates and timing of mother to infant transmission of HIV associated with breast feeding in mothers who seroconvert postnatally, and their breast milk and plasma HIV loads during and following seroconversion, compared with women who tested HIV positive at delivery. Design Prospective cohort study. Setting Urban Zimbabwe. Participants 14 110 women and infants enrolled in the Zimbabwe Vitamin A for Mothers and Babies (ZVITAMBO) trial (1997-2001). Main outcome measures Mother to child transmission of HIV, and breast milk and maternal plasma HIV load during the postpartum period. Results Among mothers who tested HIV positive at baseline and whose infant tested HIV negative with polymerase chain reaction (PCR) at six weeks (n=2870), breastfeeding associated transmission was responsible for an average of 8.96 infant infections per 100 child years of breast feeding (95% CI 7.92 to 10.14) and varied little over the breastfeeding period. Breastfeeding associated transmission for mothers who seroconverted postnatally (n=334) averaged 34.56 infant infections per 100 child years (95% CI 26.60 to 44.91) during the first nine months after maternal infection, declined to 9.50 (95% CI 3.07 to 29.47) during the next three months, and was zero thereafter. Among women who seroconverted postnatally and in whom the precise timing of infection was known (≤90 days between last negative and first positive test; n=51), 62% (8/13) of transmissions occurred in the first three months after maternal infection and breastfeeding associated transmission was 4.6 times higher than in mothers who tested HIV positive at baseline and whose infant tested HIV negative with PCR at six weeks. Median plasma HIV concentration in all mothers who seroconverted postnatally declined from 5.0 log10 copies/mL at the last negative enzyme linked immunosorbent assay (ELISA) to 4.1 log10 copies/mL at 9-12 months after infection. Breast milk HIV load in this group was 4.3 log10 copies/mL 0-30 days after infection, but rapidly declined to 2.0 log10 copies/mL and <1.5 log10 copies/mL by 31-90 days and more than 90 days, respectively. Among women whose plasma sample collected soon after delivery tested negative for HIV with ELISA but positive with PCR (n=17), 75% of their infants were infected or had died by 12 months. An estimated 18.6% to 20.4% of all breastfeeding associated transmission observed in the ZVITAMBO trial occurred among mothers who seroconverted postnatally. Conclusions Breastfeeding associated transmission is high during primary maternal HIV infection and is mirrored by a high but transient peak in breast milk HIV load. Around two thirds of breastfeeding associated transmission by women who seroconvert postnatally may occur while the mother is still in the "window period" of an antibody based test, when she would test HIV negative using one of these tests. Trial registration Clinical trials.gov NCT00198718 .